1987
DOI: 10.1111/j.1399-3054.1987.tb04301.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cyclic nucleotide phosphodiesterase activity in Phaseolus vulgaris

Abstract: Cyclic nucleotide phosphodiesterase (3′,5′‐cyclic nucleotide nucleotidohydrolase, EC 3.1.4.17) activity isolated from Phaseolus vulgaris L. cv. Limberg seedlings was partially purified and characterized by fractional (NH4)2SO4 precipitation, DEAE‐cellulose chromatography, chromatography on 3′,5′‐cAMP‐agarose, gel permeation chromatography and chromatofocusing. A crude enzyme preparation, a 30–65% (NH4)2SO4 pellet, showed an acidic pH optimum. The enzyme activity was stimulated by imidazole and divalent cations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…3.1.4.37), forming 2Ј-NMP products, and may function in tRNA splicing (Culver et al, 1994), or in unknown biological processes. Physical and catalytic properties of the tomato extracellular phosphodiesterase are markedly different from members of this class, but are strikingly similar to enzymes that have been studied during efforts to identify 3Ј:5Ј-cAMP phosphodiesterase activity as indirect evidence for the presence and function of 3Ј:5Ј-cAMP in plants (Lin and Varner, 1972;Vandepeute et al, 1973;Ashton and Polya, 1975;Brown et al, 1977;Junker et al, 1977Junker et al, , 1979Junker et al, , 1980Zan-Kowalczewska et al, 1984;Dupon et al, 1987;Chiatante et al, 1988;Gangwani et al, 1994). However, properties of most plant cyclic nucleotide phosphodiesterases characterized during those investigations have been found to differ significantly from animal and bacterial 3Ј:5Ј-cyclic nucleotide-3Ј-phosphodiesterases.…”
Section: Discussionmentioning
confidence: 99%
“…3.1.4.37), forming 2Ј-NMP products, and may function in tRNA splicing (Culver et al, 1994), or in unknown biological processes. Physical and catalytic properties of the tomato extracellular phosphodiesterase are markedly different from members of this class, but are strikingly similar to enzymes that have been studied during efforts to identify 3Ј:5Ј-cAMP phosphodiesterase activity as indirect evidence for the presence and function of 3Ј:5Ј-cAMP in plants (Lin and Varner, 1972;Vandepeute et al, 1973;Ashton and Polya, 1975;Brown et al, 1977;Junker et al, 1977Junker et al, , 1979Junker et al, , 1980Zan-Kowalczewska et al, 1984;Dupon et al, 1987;Chiatante et al, 1988;Gangwani et al, 1994). However, properties of most plant cyclic nucleotide phosphodiesterases characterized during those investigations have been found to differ significantly from animal and bacterial 3Ј:5Ј-cyclic nucleotide-3Ј-phosphodiesterases.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the observation that in at least one plant species the phosphodiesterase is present in a complex also containing nucleotidase suggests that identification of one or other mononucleotide isomer as the major product of phosphodiesterase activity might not be as clearcut as it seems at first. For example a 3h,5h-cAMP phosphodiesterase activity from Phaseolus vulgaris seedlings 7 d old had an acidic pH optimum, was strongly stimulated by Mn# + , Mg# + and Ca# + and imidazole, was inhibited by NaF, PP i and Fe$ + and was insensitive to butylmethylxanthine ; purification away from a contaminating monoesterase activity revealed that the protein hydrolysed the 3h-ester linkage exclusively (Dupon et al, 1987).…”
Section: mentioning
confidence: 99%